Tumors of the Jugular Foramen - Ramina, MD, PhD, Ricardo; Tatagiba, MD, PhD, Marcos Soares (Springer International Publishing : Imprint: Springer, 2017)
This book covers all aspects of the diagnosis and treatment of tumors of the jugular foramen - cranial base lesions that present particular diagnostic and management difficulties and remain challenging to remove despite advances in surgery and interventional neuroradiology. The authors have developed novel concepts and surgical techniques relating to management of the facial nerve, reconstruction of the cranial base, and resection of large tumors with intra- and extracranial extension. These techniques, as well as anatomic studies in cadavers, are presented by means of surgical photographs, illustrations, and videos. Tumors of the Jugular Foramen will be of interest to all specialists involved in the management of these challenging tumors, including neurosurgeons, ENT surgeons, neuroradiologists, neurologists, neurointensivists, radiotherapists, oncologists, and physiotherapists.
Keywords: Medicine.; Neuroradiology.; Neurology.; Neurosurgery.; Otorhinolaryngology.; elektronické knihy; electronic books